2006
DOI: 10.4049/jimmunol.176.3.1916
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Progenitor Epithelial Cells Traffic via CXCR4/CXCL12 in Response to Airway Injury

Abstract: Recipient airway epithelial cells are found in human sex-mismatched lung transplants, implying that circulating progenitor epithelial cells contribute to the repair of the airway epithelium. Markers of circulating progenitor epithelial cells and mechanisms for their trafficking remain to be elucidated. We demonstrate that a population of progenitor epithelial cells exists in the bone marrow and the circulation of mice that is positive for the early epithelial marker cytokeratin 5 (CK5) and the chemokine recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
120
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(128 citation statements)
references
References 38 publications
8
120
0
Order By: Relevance
“…Several recent studies have demonstrated that culturing fetal lung cells in artificial three dimensional matrices results in formation of alveolar-like structures (28)(29). This suggests that culture of stem cells in an artificial scaffolding in medium conducive to lung epithleial development may be a robust means of lung regeneration than achieved with routine tissue culturing [29][30][31][32][33].…”
Section: Lung Repair and Remodeling With Adult Bone Marrow-derived Stmentioning
confidence: 94%
See 1 more Smart Citation
“…Several recent studies have demonstrated that culturing fetal lung cells in artificial three dimensional matrices results in formation of alveolar-like structures (28)(29). This suggests that culture of stem cells in an artificial scaffolding in medium conducive to lung epithleial development may be a robust means of lung regeneration than achieved with routine tissue culturing [29][30][31][32][33].…”
Section: Lung Repair and Remodeling With Adult Bone Marrow-derived Stmentioning
confidence: 94%
“…However, as yet, there is little data demonstrating this can be effectively accomplished. Other populations of marrow-derived cells may yet be found to participate in structural lung remodeling or regeneration and are subjects of active study [28].…”
Section: Lung Repair and Remodeling With Adult Bone Marrow-derived Stmentioning
confidence: 99%
“…HSC and other nonhematopoietic stem cells are actively chemoattracted by factors secreted by BM stroma cells and osteoblasts (e.g., stromal derived factor-1 [SDF-1] and hepatocyte growth factor [HGF]) and colonize marrow by the end of the second and the beginning of the third trimester of gestation (Kmiecik et al, 1992;Ma et al, 1998;Nagasawa, 2000;Taichman et al, 2001). Accumulating evidence suggests that these nonhematopoietic stem cells residing in the BM play some role in the homeostasis/turnover of peripheral tissues and if needed could be released/mobilized from the BM into circulation during tissue injury and stress, thus facilitating the regeneration of damaged organs (LaBarge and Blau, 2002;Kale et al, 2003;Kollet et al, 2003;Abbott et al, 2004;Kucia et al, 2004Kucia et al, , 2006cWojakowski et al, 2004;Long et al, 2005;Gomperts et al, 2006). It is also possible that, in steady state conditions, they shuttle at very low level between BM and stem cell niches in peripheral organs/tissues.…”
Section: Introductionmentioning
confidence: 99%
“…97,98 This mechanism had been proposed for heart infarct, 39,99 stroke, 100,101 liver damage, 102 kidney damage, 43,103 pancreatic damage, 104 skeletal muscle injury, 105 bone fractures 106 and lung damage. 107 Accordingly, during these various organ/tissue injury models, there were circulating cells identified in PB that express markers for endothelial-, mesenchymal-, cardiac-, skeletal muscle-, liver-, kidney, neural-and bone-NSC. The presence of non-HSC was also reported in mobilized PB during pharmacological mobilization by G-CSF or in cord blood, which could be considered as neonatal-mobilized PB in response to delivery stress.…”
Section: Concept Of Circulation Of Cxcr4 þ Non-hematopoietic Nscmentioning
confidence: 99%